An official nomenclature for the major histocompatibility complex allele sequences from the domestic goat (Capra hircus). (12th December 2018) - Ballingall, Keith T.; Todd, Helen
Abstract : Official allelic nomenclature and corresponding databases of validated major histocompatibility complex (MHC) alleles from most of the major species of farmed livestock are now represented on the IPD‐MHC Database. The major exception is the domestic goat ( Capra hircus ) which can lead to confusion in the research community. Here, we propose to start the process of developing such a resource which will support the research community's interests in livestock population genetics, infectious disease research, vaccine development and comparative studies. In this manuscript, we assign the official nomenclature for the major transcribed and highly polymorphic MHC class II DRB1 locus. Additional class II loci including DRA and DQ and MHC class I loci will be added in the future.